Tuberculosis: Role of Nuclear Medicine and Molecular Imaging With Potential Impact of Neutrophil-Specific Tracers - More, Stuart; Marakalala, Mohlopheni J.; Sathekge, Michael (Frontiers in Medicine, 2021)
With Tuberculosis (TB) affecting millions of people, novel imaging modalities and tools, particularly nuclear medicine and molecular imaging, have grown with greater interest to assess the biology of the tuberculous granuloma and evolution thereof. Much early work has been performed at the preclinical level using gamma single photon emission computed tomography (SPECT) agents exploiting certain characteristics of Mycobacterium tuberculosis (MTb). Both antituberculous SPECT and positron emission tomography (PET) agents have been utilised to characterise MTb. . Other PET tracers have been utilised to help characterise the biology of MTb (including Gallium 68-labelled radiopharmaceuticals. Of all the tracers, 2-[18F]FDG has been studied extensively over the last two decades in many aspects of the treatment paradigm of TB: at diagnosis, staging, response assessment, restaging and in potentially predicting outcome of patients with latent TB infection. Its lower specificity in being able to distinguish different inflammatory cell types in the granuloma has garnered interest in reviewing more specific agents that can portend prognostic implications in the management of MTb. With the neutrophil being a cell type that portends this poorer prognosis, imaging this cell type may be able to answer more accurately questions relating to the tuberculous granuloma transmissivity and may help in characterising patients who may be at risk of developing active TB. The formyl peptide receptor 1(FPR1) expressed by neutrophils, is a key marker in this process and is a potential target to characterise these areas. The preclinical work regarding the role of radiolabelled N-cinnamoyl –F-(D) L – F – (D) –L F (cFLFLF) (which is an antagonist for FPR1), using Technetium 99m labelled conjugates and more recently radiolabelled with Gallium 68 and Copper 64 is discussed. It is the hope that further work with this tracer may accelerate its potential to be utilised in responding to many of the current diagnostic dilemmas and challenges in TB management, thereby making the tracer a translatable option in routine clinical care.